POLYDACTYLY OF THUMB – WASSEL TYPE IV: A CASE REPORT - Hariantana Hamid, Agus Roy Rusly; Padmasari, Tiesya Andira (Jurnal Abdimas Bina Bangsa, 2024)
Polydactyly is a congenital condition that manifests in a variety of ways, ranging from minor splitting to a fully duplicated thumb. When duplication occurs alone, it is typically unilateral and infrequent. Polydactyly is a deformity of the human limb that is distinguished by the presence of more than the average number of fingers or toes. It is thought to be one of the most common inherited hand illnesses. Polydactyly can be classified into three types based on the anatomical placement of the duplicated digits: preaxial, postaxial, and central or mesoaxial. Polydactyly can be classified into three types based on the anatomical placement of the duplicated digits: preaxial, postaxial, and mesoaxial. This case report describes an otherwise healthy 8-years-old female with isolated left hand preaxial polydactyly. She then underwent surgical correction, and the overnumbered thumb was removed, along with thorough bone and soft tissue repair. Polydactyly is the most prevalent congenital digital abnormality of the hand and foot. It may arise alone or as part of a condition. Surgery is required to generate a single functional thumb and is recommended to improve appearance. An optimum finger must be constructed by combining skin, nail, bone, ligament, and muscular aspects. In this situation, surgery was required to leave the student with a single working thumb